2009
DOI: 10.1128/jvi.01186-09
|View full text |Cite
|
Sign up to set email alerts
|

IRF3 Inhibition by Rotavirus NSP1 Is Host Cell and Virus Strain Dependent but Independent of NSP1 Proteasomal Degradation

Abstract: Rotavirus host range restriction forms a basis for strain attenuation although the underlying mechanisms are unclear. In mouse fibroblasts, the inability of rotavirus NSP1 to mediate interferon (IFN) regulatory factor 3 (IRF3) degradation correlates with IFN-dependent restricted replication of the bovine UK strain but not the mouse EW and simian RRV strains. We found that UK NSP1 is unable to degrade IRF3 when expressed in murine NIH 3T3 cells in contrast to the EW and RRV NSP1 proteins. Surprisingly, UK NSP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
103
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(115 citation statements)
references
References 55 publications
(107 reference statements)
11
103
1
Order By: Relevance
“…Although a wealth of knowledge has been gained from mouse studies with nonhuman enteric viruses, these models do not account for evolutionary differences in host and pathogen. Subtle but possibly important differences exist between human and mouse type I and III IFN systems and between human and mouse rotaviruses (18,(35)(36)(37)(38), necessitating functional studies of interactions between human host cells and human enteric pathogens.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Although a wealth of knowledge has been gained from mouse studies with nonhuman enteric viruses, these models do not account for evolutionary differences in host and pathogen. Subtle but possibly important differences exist between human and mouse type I and III IFN systems and between human and mouse rotaviruses (18,(35)(36)(37)(38), necessitating functional studies of interactions between human host cells and human enteric pathogens.…”
Section: Significancementioning
confidence: 99%
“…In addition, HRV generally replicates to lower titers than animal rotaviruses in transformed cell lines (2). Therefore, most knowledge of rotavirus-host interactions comes from studies that analyzed animal rotavirus replication in animal models or in transformed cell lines (15)(16)(17)(18). Induction of the adaptive immune system and secretion of IgA are critical factors in protecting the host against rotavirus infection based on in vivo models of animal rotavirus infection (19,20).…”
mentioning
confidence: 99%
“…In a mouse model of rotavirus infection, RRV replication in gallbladder epithelia correlates with its ability to suppress the IFN response (N. Feng et al, submitted for publication). The rotavirus gene segment encoding the nonstructural protein 1 (NSP1) is an important determinant of host restriction of viral replication both in vitro (17,53) and in vivo (9). Specifically, we along with others have reported a role for NSP1 in regulating the ability of rotavirus to efficiently cause diarrhea in mice (9), spread from animal to animal (9), replicate in vivo and in vitro (4,(15)(16)(17), and antagonize IFN (4,5,17,24,25,53).…”
mentioning
confidence: 99%
“…In primary mouse embryonic fibroblasts (MEFs), several heterologous (nonmurine) rotavirus strains, including the bovine UK strain, are replication restricted by the host type I interferon (IFN) response (17,53). In contrast, replication of homologous murine EW virus and the heterologous simian rhesus rotavirus (RRV) strain is insensitive to the presence of the interferon system.…”
mentioning
confidence: 99%
“…A previous study performed by Feng et al (9) demonstrated that both VP4 and NSP1 genes from RRV were required for replication within the mouse biliary tract when comparing RRV and the bovine strain UK. NSP1 has previously been shown to inhibit interferon regulatory factors to suppress type I interferon production (8,22). To date, not all of the rotavirus strains examined in this study have had their NSP1 gene sequenced; thus we cannot rule out the potential involvement of NSP1 in the strains' ability to replicate within biliary cells.…”
Section: Discussionmentioning
confidence: 91%